Corticosteroid Pulses for Hospitalized Patients with COVID-19: Effects on Mortality. (13th March 2021) - Cusacovich, Ivan; Aparisi, Álvaro; Marcos, Miguel; Ybarra-Falcón, Cristina; Iglesias-Echevarria, Carolina; Lopez-Veloso, Maria; Barraza-Vengoechea, Julio; Dueñas, Carlos; Juarros Martínez, Santiago Antonio; Rodríguez-Alonso, Beatriz; Martín-Oterino, José-Ángel; Montero-Baladia, Miguel; et al.
Abstract : Objectives . To assess the influence of corticosteroid pulses on 60-day mortality in hospitalized patients with severe COVID-19. Methods . We designed a multicenter retrospective cohort study in three teaching hospitals of Castilla y León, Spain (865, 096 people). We selected patients with confirmed COVID-19 and lung involvement with a pO2/FiO2<300, excluding those exposed to immunosuppressors before or during hospitalization, patients terminally ill at admission, or those who died in the first 24 hours. We performed a propensity score matching (PSM) adjusting covariates that modify the probability of being treated. Then, we used a Cox regression model in the PSM group to consider factors affecting mortality. Results . From 2933 patients, 257 fulfilled the inclusion and exclusion criteria. 124 patients were on corticosteroid pulses (250 mg of methylprednisolone for three days), and 133 were not. 30.3% (37/122) of patients died in the corticosteroid pulse group and 42.9% (57/133) in the nonexposed cohort. These differences (12.6%, 95% CI [8·54-16.65]) were statically significant (log-rank 4.72, p = 0, 03 ). We performed PSM using the exact method. Mortality differences remained in the PSM group (log-rank 5.31, p = 0.021 ) and were still significant after a Cox regression model (HR for corticosteroid pulses 0.561; p = 0.039 ). Conclusions . This study provides evidence about treatment with corticosteroid pulses in severe COVID-19 that might significantly reduce mortality. Strict inclusion and exclusion criteria with that selection process set a reliable frame to compare mortality in both the exposed and nonexposed groups.